Kekristenan dan Violence: Just War dan Tradisi Kristen - Benyamin Fleming Intan (Societas Dei: Jurnal Agama dan Masyarakat, 2014)
ABSTRACT: After man has sinned, violence cannot be separated from human life. As Christianity comes into contact with violence, it generates a theory of just-war in responding against injustice. The applications of just-war theory are not only limited to Christian circle, but has reached wider groups. Just-war has become a guidance for non-Christian philosophers and politicians to fight oppressors and to uphold justice. This paper discribes the idea of just-war in Christians tradition, firstly by exploring the legitimacy of war in the light of the Word of God, and secondly by comparing it to the holy war in the context of the Old Testament. To better understand the views of the church leaders about just-war this paper will also discuss the criticisms against the theory. The author believes that the presence of just-war theory is crucial in the midst of this sinful world.Â KEYWORDS:Â violence, the legitimacy of war, just-war, holy war, peace, justice, Christian love